PENGEMBANGAN MEDIA PEMBELAJARAN ASPEK KEBAHASAN TEKS OBSERVASI BERBASIS APLIKASI POWTOON KELAS X MAS PROYEK UNIVA MEDAN - Sri Ningsih; Rika Kartika; Nila Safina; Ratna Soraya (Jurnal Dialect, 2024)
This study aims to determine the development of feasibility and effectiveness of video learning media products on the Indonesian material "Text of the Observation Report". This research uses a 4D development method by Thiagarajan which consists of four stages, namely define, design, development, and dissemination. The instrument in this study used questionnaires addressed to material expert validators and learning media experts, Indonesian teachers and a number of 23 grade X MIA1 MAS students of the Univa Medan Project to determine the analysis of student needs on learning media. The data analysis technique used in calculating the percentage of indicators to determine the feasibility of learning media is quantitative descriptive analysis. The results of video learning media feasibility validation based on validation research by material I were obtained 88% got the value criteria "Very Feasible", the results of the material II validation assessment were obtained 85% got the value criteria  "Very Feasible" Field implementation test with 23 students of grade X MIA1 MAS Univa Medan Project obtained 88% getting the value criteria "Very Feasible.The stage of the results of the effectiveness of teaching materials for lecture texts assisted by theme card media was carried out by means of evaluation tests on question sheets to be able to measure the effectiveness of learning media. The results of the evaluation obtained the criteria of "Very Effective" value with a percentage (93%).